2018
DOI: 10.5604/01.3001.0012.2828
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of multistage artificial aging parameters on Al-Cu alloy mechanical properties

Abstract: Purpose: This research is aimed to describe heat treatment process by using multistage artificial aging for Al-Cu alloy with Taguchi method in Minitab 16 to optimize the heat treatment parameters. This research conducted due to the applied of aluminium alloy in automotive industrial and aircraft industrial that has good properties for fabrication. Design/methodology/approach: Methodology that use in this paper is experimental design with statistical approach. Three controllable parameters were selected, they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Aluminum is one type of non-ferrous metal that is most widely used in the world, especially in the automotive, aircraft industry, manufacturing industry, and household appliances, this is because aluminum has several advantages such as being lightweight, resistant to corrosion, cheap, and easy to be formed [1]. However, when compared to other commercial metals, aluminum has a relatively lower hardness and wear resistance [2,3]. Previous research about the use of anodizing treatment showed changes in hardness with variations in electrolyte solutions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum is one type of non-ferrous metal that is most widely used in the world, especially in the automotive, aircraft industry, manufacturing industry, and household appliances, this is because aluminum has several advantages such as being lightweight, resistant to corrosion, cheap, and easy to be formed [1]. However, when compared to other commercial metals, aluminum has a relatively lower hardness and wear resistance [2,3]. Previous research about the use of anodizing treatment showed changes in hardness with variations in electrolyte solutions [4].…”
Section: Introductionmentioning
confidence: 99%